Multiscale approach to (micro)porosity quantification in continental spring carbonate facies: Case study from the Cakmak quarry (Denizli, Turkey). (24th July 2016) - De Boever, Eva; Foubert, Anneleen; Oligschlaeger, Dirk; Claes, Steven; Soete, Jeroen; Bertier, Pieter; Özkul, Mehmet; Virgone, Aurélien; Swennen, Rudy
Abstract: Carbonate spring deposits gained renewed interest as potential contributors to subsurface reservoirs and as continental archives of environmental changes. In contrast to their fabrics, petrophysical characteristics – and especially the importance of microporosity (< 1µm) – are less understood. This study presents the combination of advanced petrophysical and imaging techniques to investigate the pore network characteristics of three, common and widespread spring carbonate facies, as exposed in the Pleistocene Cakmak quarry (Denizli, Turkey): the extended Pond, the dipping crystalline Proximal Slope Facies and the draping Apron and Channel Facies deposits formed by encrustation of biological substrate. Integrating mercury injection capillary pressure, bulk and diffusion Nuclear Magnetic Resonance (NMR), NMR profiling and Brunauer–Emmett–Teller (BET) measurements with microscopy and micro‐computer tomography (µ‐CT), shows that NMR T2 distributions systematically display a single group of micro‐sized pore bodies, making up between 6 and 33% of the pore space (average NMR T2 cut‐off value: 62 ms). Micropore bodies are systematically located within cloudy crystal cores of granular and dendritic crystal textures in all facies. The investigated properties therefore do not reveal differences in micropore size or shape with respect to more or less biology‐associated facies. The pore network of the travertine facies is distinctive in terms of (i) the percentage of microporosity, (ii) the connectivity of micropores with meso‐ to macropores, and (ii) the degree of heterogeneity at micro‐ and macroscale. Results show that an approach involving different NMR experiments provided the most complete view on the 3‐D pore network especially when microporosity and connectivity are of interest. Key Points: An approach of advanced petrophysical and imaging techniques investigating 3‐D pore networks in travertine facies NMR T2 distributions display a single group of micro‐sized pore bodies, making up between 6 and 33% of the pore space The pore network of 3 travertine facies is distinctive in microporosity%, micro‐ to macropore connectivity and degree of heterogeneity